Reducing Hunger with Payments for Ecosystem Services : Experimental Evidence from Burkina Faso - Adjognon, Guigonan Serge; van Soest, Daan; Guthoff, Jonas (World Bank, Washington, DC, 2019)
Does financial compensation for providing environmental conservation, improve the food security of the rural poor in the drylands of Sub-Saharan Africa? This paper explores this question using data from a randomized controlled trial of a large scale reforestation implemented by the Government of Burkina Faso. Members of communities located around selected protected forests were invited to plant indigenous tree species on degraded areas, and to take care of their maintenance. The financial compensation they would receive depended on the number of trees still alive a year later. The vast majority of the community members participating in the project were farmers, and the timing of the payments coincided with the lean season, when most farmers were at risk of food insecurity. Compared with the control group, the project's participants' households reported 12 percent higher food consumption expenditures, and a reduction in moderate and severe food insecurity by 35 percent to 60 percent. The transfers received were spent mostly on cereals, meat, and pulses, with no evidence of increased consumption of temptation goods.